1999
DOI: 10.1046/j.1365-2419.1999.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of community structure of Copepoda related to El Niño 1982–83 and 1987–88 along the west coast of Baja California Peninsula, Mexico

Abstract: Copepod community structure and abundance of the most abundant species were studied during 15 cruises made between 1982 and 1989 along the west coast of the Baja California Peninsula, Mexico. The number of species and species diversity (Shannon’s index) for each sampling station of the oceanographic cruises were obtained. Though the zone was dominated during the year by the tropical copepod component, similarities between El Niño 1982–83 and 1987–88 were observed. Tropical‐equatorial populations were added to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
10
0
3
Order By: Relevance
“… (a) Multivariate El Niño‐Southern Oscillation Index (dashed line) and SST anomalies (solid line) along the Pacific Coast of Baja California Sur, Mexico 1982–88 (from Gómez‐Gutiérrez et al. , 1995; Hernández‐Trujillo, 1999). (b) Monthly average zooplankton biomass (bars), and upwelling (line; m 3 s −1 per 100 m coastline).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… (a) Multivariate El Niño‐Southern Oscillation Index (dashed line) and SST anomalies (solid line) along the Pacific Coast of Baja California Sur, Mexico 1982–88 (from Gómez‐Gutiérrez et al. , 1995; Hernández‐Trujillo, 1999). (b) Monthly average zooplankton biomass (bars), and upwelling (line; m 3 s −1 per 100 m coastline).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies of plankton populations off Baja California Sur showed that the number of tropical species was relatively constant (Gómez‐Gutiérrez et al. , 1995; Hernández‐Trujillo, 1999). Nevertheless, there is high inter‐annual variation in species composition that could be related to changes in the California Current system and environmental shifts like El Niño.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hernández-Trujillo (1999) reported changes in the copepod community off south Baja California throughout the period 1982 to 1989. The overlap of this area with the IMECOCAL grid is confined to the southern locations near the coast.…”
Section: Discussionmentioning
confidence: 99%